Downstream Processing of Itraconazole:HPMCAS Amorphous Solid Dispersion: From Hot-Melt Extrudate to Tablet Using a Quality by Design Approach - Saurabh M Mishra; Margarethe Richter; Luis Mejia; Andreas Sauer (MDPI AG, 2022)
The downstream processing of hot-melt extruded amorphous solid dispersions (ASDs) into tablets is challenging due to the low tabletability of milled ASDs. Typically, the extrudate strand is sized before milling, as the strand cannot be fed directly into the milling system. At the lab scale, the strand can be sized by hand-cutting before milling. For scaling up, pelletizers or chill roll and flaker systems can be used to break strands. Due to the different techniques used, differences in milling and tablet compaction are to be expected. We present a systematic study of the milling and tableting of an extruded ASD of itraconazole with hypromellose acetate succinate (HPMCAS) as a carrier polymer. The strand was sized using different techniques at the end of the extruder barrel (hand-cutting, pelletizer, or chill roll and flaker) before being milled at varying milling speeds with varying screen sizes. The effects of these variables (sizing technology, milling speed, and screen size) on the critical quality attributes (CQAs) of the milled ASD, such as yield, mean particle size (D50), tablet compaction characteristics, and tablet dissolution, were established using response surface methodology. It was found that the CQAs varied according to sizing technology, with chill roll flakes showing the highest percentage yield, the lowest D50, and the highest tabletability and dissolution rate for itraconazole. Pearson correlation coefficient tests indicated D50 as the most important CQA related to tabletability and dissolution. For certain milling conditions, the milling of hand-cut filaments results in similar particle size distributions (PSDs) to the milling of pellets or chill roll flakes.